If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6x-7=5x-61
We move all terms to the left:
6x-7-(5x-61)=0
We get rid of parentheses
6x-5x+61-7=0
We add all the numbers together, and all the variables
x+54=0
We move all terms containing x to the left, all other terms to the right
x=-54
| m/3-6=14 | | -3x+3=9-5x | | 18x+7=45 | | 5x+5=41-4x | | 8x-3-4x=3(8x-1 | | -9-10y=1 | | 24x-22=-4(1-6x | | 5-3(x+4)=5 | | 2(x+2)=3x-11 | | 3x/5+8=2 | | 2p-p-p+3p-2p=14 | | (3x-2)(x-8)=(1-2x)(x+6) | | 175-2d=755 | | 3x+3=5+9x | | 14=2-4r | | 12-5x=-8x+15 | | 3m+2(m-4)=17 | | -7t+15t-(-20t)-16t=12 | | 4h+h+3=23 | | 6(3a-4)=-4(a+6) | | 10x-3x+5=36 | | 4r–2=14 | | 34495X=100001-10000x | | 42=4x+6 | | 5x+7-9x=4x-2+x | | 3(15-m)=12 | | 5x-9=2x+40 | | c=8+9 | | 71m-22-6m=-13+5 | | 6x+2(3x-4)=10(x+1) | | -32x=21x-22 | | r^2+12r=39 |